EFFECT OF THE COMBINED ANTIHYPERTENSIVE THERAPY WITH TARGET BLOOD PRESSURE ACHIEVEMENT ON INTRARENAL BLOOD FLOW IN PATIENTS WITH TYPE 2 DIABETES - O. A. Koshel'skaya; O. A. Zhuravleva (Столичная издательская компания, 2015)
Aim. To compare the dynamics of intrarenal vascular resistance (IRVR), circadian blood pressure (BP) profile and glomerular filtration rate (GFR) in patients with arterial hypertension (HT) and type 2 diabetes mellitus (DM) who achieved the target BP levels (<130/80 mmHg) due to long-term combined antihypertensive therapy with or without renin-angiotensin-aldosterone system (RAAS) inhibitors. Material and methods. Patients (n=61) with HT and DM without clinical symptoms of nephroangiopathy were included into the open randomized study , 59 of these patients completed study. Patients of Group 1 (n=41) received therapy with valsartan (n=20), 80-160 mg/day , or perindopril (n=21), 5-10 mg/day , in combination with indapamide retard, 1.5 mg/day , and amlodipine, 5-10 mg/day. Patients of Group 2 (n=18) received amlodipine (5-10 mg/day) in combination with indapamide retard (1.5 mg/day) and metoprolol succinate (50-100 mg/day). Initially and after 30-32 weeks of therapy the following examinations were performed: duplex ultrasound scanning of the main renal (MRA) and intrarenal arteries (IRA) with resistive index (RI) calculation, ambulatory BP monitoring (ABPM), GFR calculation (by Cockcroft-Gault formula). Results. The target BP levels were achieved in all patients of both groups. Patient's baseline characteristics including age, sex, duration of disease, office BP , GFR, RI in MRA and IRA did not differ in the groups as well as decrease in office BP due to treatment. However patients of Group 2 had higher levels of systolic BP and systolic BP load at night time than these in patients of Group 1 during all period of the treatment. In patients of Group 2 RI in MRA and arcuate IRA were increased from 0.67±0.06 to 0.69±0.06 (p=0.02) and from 0.62±0.07 to 0.64±0.06 (p=0.02), respectively. The increase in IRA was positively associated with systolic BP at night time in these patients (r=0.6; p=0.01). There were no significant changes of IRA in Group 1 totally. At the same time, initially high IRVR decreased in 61% of patients. GFR increased in patients of Group 2 (p=0.01), while dynamics of GFR was not found in patients of Group 1. Conclusion. Achievement of target BP levels due to antihypertensive therapy not including RAAS inhibitors resulted in increase in IRVR that associated with the lack of systolic BP reduction at night time.